A case report on Kawasaki disease - P., Muhammed Nishad; S., S. Mohamed Ashik Ali; Priya, A.; Chander, K. Arun (International Journal of Basic & Clinical Pharmacology, 2022)
Kawasaki disease (KD) is an acute vasculitis of children that leads to coronary artery aneurysms in ≈ 25 of untreated cases. It has been reported worldwide and is the leading cause of acquired heart disorder in children in developed countries. The diagnosis of KD is made on basis on the clinical findings. Atypical KD includes patients who don't meet all the criteria for opinion. The main complication of Kawasaki complaint is coronary aneurysm, and the treatment is intravenous immunoglobulin and aspirin. Another dose of immunoglobulin is given if the patient doesn't ameliorate, and several other treatment options have been proposed over the last many years as alternate and third line options. The AHA criteria, which incorporate suggestions for laboratory tests and early echocardiography, are helpful for diagnosing incomplete KD. Diagnosis is based on the presence of fever lasting longer than 5 days and four of five specific clinical criteria. In Japan, at least five of six criteria (fever and five other clinical criteria) should be fulfilled for the determination of KD. From the Japanese circulation society joint working groups criteria (JCS 2008, Guidelines for diagnosis and management of cardiovascular sequela in KD), KD can be diagnosed indeed when fever lasts lesser than 5 days. Though, according to the American heart association (AHA) criteria, fever lasting more than 5 days is essential for KD diagnosis. The use of intravenous immunoglobulin is well established in KD. Aspirin has been used in KD for anti-inflammatory effect, and low-dose aspirin is recommended to reduce the risk of thrombosis.